Whole blood transfusion versus component therapy in adult trauma patients with acute major haemorrhage. Issue 6 (6th May 2020) - Avery, Pascale; Morton, Sarah; Tucker, Harriet; Green, Laura; Weaver, Anne; Davenport, Ross
Abstract : Objective: In the era of damage control resuscitation of trauma patients with acute major haemorrhage, transfusion practice has evolved to blood component (component therapy) administered in a ratio that closely approximates whole blood (WB). However, there is a paucity of evidence supporting the optimal transfusion strategy in these patients. The primary objective was therefore to establish if there is an improvement in survival at 30 days with the use of WB transfusion compared with blood component therapy in adult trauma patients with acute major haemorrhage. Methodology: A systematic literature search was performed on 15 December 2019 to identify studies comparing WB transfusion with component therapy in adult trauma patients and mortality at 30 days. Studies which did not report mortality were excluded. Methodological quality of included studies was interpreted using the Cochrane risk of bias tool, and rated using the Grading of Recommendations Assessment, Development and Evaluation approach. Results: Search of the databases identified 1885 records, and six studies met the inclusion criteria involving 3255 patients. Of the three studies reporting 30-day mortality (one randomised controlled trial (moderate evidence) and two retrospective (low and very low evidence, respectively)), only one study demonstrated a statistically significant difference between WB and component therapy, and two found no statistical difference. Two retrospective studies reporting in-hospital mortality found no statistical difference in unadjusted mortality, but both reported statistically significant logistic regression analyses demonstrating that those with a WB transfusion strategy were less likely to die. Conclusion: Recognising the limitations of this systematic review relating to the poor-quality evidence and limited number of included trials, it does not provide evidence to support or reject use of WB transfusion compared with component therapy for adult trauma patients with acute major haemorrhage. PROSPERO registration number: CRD42019131406.